A Mesoarchean shift in uranium isotope systematics. (1st October 2018) - Wang, Xiangli; Planavsky, Noah J.; Hofmann, Axel; Saupe, Erin E.; De Corte, Brian P.; Philippot, Pascal; LaLonde, Stefan V.; Jemison, Noah E.; Zou, Huijuan; Ossa, Frantz Ossa; Rybacki, Kyle; Alfimova, Nadezhda; et al.
Abstract: Oxygenic photosynthesis fundamentally transformed all major biogeochemical cycles and increased the size and complexity of Earth's biosphere. However, there is still debate about when this metabolism evolved. As oxygenic photosynthesis is the only significant source of O2 at Earth's surface, O2 -sensitive trace element enrichments and isotopic signatures in Archean sedimentary rocks can potentially be used to determine the onset of oxygenic photosynthesis by tracking shifts in the oxidative capacity of Earth's surface environment. Here, we present an extensive new Archean U isotope record from iron formations, organic-rich shales, and paleosols. Variability in δ 238 U values gradually increased from Archean to Phanerozoic, consistent with current view of gradual oxidation of Earth's surface. In addition, statistical analysis on available δ 238 U data indicates a turning point of δ 238 U variability at roughly 3.0 billon years ago. We suggest that such a turning point in δ 238 U variability indicates the initiation of relatively large-scale oxidative weathering of U(IV)-bearing minerals, implying that oxygenic photosynthesis may have evolved before 3.0 billion years ago.